A Model of Women Literacy Preservation through Koran Ibu Program - Ikka Kartika Abbas Fauzi (Intelektual Pustaka Media Utama, 2016)
The effect of literacy education is often disappointing, because many participants do not practice their literacy so that it becomes dull. Government has done efforts to preserve literariness through Koran Ibu program. This program is an effort to improve women literacy which is implemented after basic and advanced literacy education through the activity of journalism. The research focus is the improvement of literacy ability of women through Koran Ibu using with case study method. The research’s subjetcs are 20 housewives who have completed the basic and advanced literacy education program. The result of the research shows that participants significantly develops the literacy skills, it is indicated from that they are able to participate in Koran Ibu’s rubrics with their literary works based on reportage and personal experience. The program is succesful due to the coordination among local participants (Lurah, Camat, PKK of local level), the cooperation with proper stakeholders (university and local tutor), the appropriate approach of adult learning, flexible implementation strategy but planned, and the routine evaluation.